Storia delle ricerche paletnologiche nel territorio di Varese - Pearce, Mark (Nomos Edizioni, 2017)
A history of prehistoric studies in the north Italian province of Varese. The province of Varese saw some of the pioneering work in prehistory in Italy in the 19th century, and many key figures in the history of the discipline have done work in the province.